PENGARUH KEPEMILIKAN INSTITUSIONAL TERHADAP IMPLEMENTASI STRATEGI PROSPEKTOR DAN DEFENDER - Prasetyo, Adi (Journal of Innovation in Business and Economics, 2014)
The purpose of this study is to proof that the institution stock holders have a significant effect on implementation of typology organizational strategy. Furthermore, it showed that the domination of institution stock holders have significant influence on implementation of prospector typology and defender strategy. Institutional stock holders measured by percentage of stock holders were published by the Indonesian Capital Market Directory (ICMD). On the other hand, in order to determine prospector typology and defender strategy, the researcher used four indicators as proxy, such as: KARPEN, PBV, CETA, and CEMVE.